1983
DOI: 10.1007/bf00581053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded vagal blockade and pulmonary volume on tonic inspiratory activity in rabbits

Abstract: Reflex respiratory responses to increased and decreased tracheal pressure have been studied at bilateral local vagus temperatures between 30 degrees C and 0 degrees C in anaesthetized spontaneously breathing rabbits. The temperature of each cervical vagus nerve was governed by separate thermodes, which were cooled by Peltier elements and heated by transistors. In this study, the lowest activity level of the diaphragm during expiration was considered to reflect tonic inspiratory activity. As an indicator for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In rabbits, ETIA has been evoked in response to a decreased Ptr [7] and after administration of histamine, both in the diaphragm and in ICMs [10]. In man, ETIA has been observed after administration of histamine [6].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In rabbits, ETIA has been evoked in response to a decreased Ptr [7] and after administration of histamine, both in the diaphragm and in ICMs [10]. In man, ETIA has been observed after administration of histamine [6].…”
Section: Discussionmentioning
confidence: 96%
“…These studies have shown a significant correlation between the increase in thoracic gas volume and the increase in ETIA. Recent studies have shown that, with intact vagus nerves, lowering of tracheal pressure (P tr ) could evoke ETIA in rabbits [7] and cats [8,9]. Stimulation of thin vagal afferents by administration of histamine increased the magnitude of ETIA in rabbits [10].…”
mentioning
confidence: 99%
“…The present study originated from an earlier one [ 10] in which lung inflation as well as deflation reflexly increased the tonic activity of the diaphragm after bilateral local vagus cooling to 8 ~ We hypothesized that the vagal A fibres were completely blocked at 8 ~ and that the C fibres conducted the reflex stimuli. The present results are consistent with this hypothesis since in eight nerves the A fibres were completely blocked at 8 ~ in the other two this occurred at 7.0 and 6.8 ~ (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Vagotomy abolished these effects. Previous studies in the rabbit [6,10] showed that bilateral local vagus cooling to 8 ~ blocked the Hering-Breuer reflex and increased the tonic activity of the diaphragm, that is the level of activity to which the diaphragm returns during expiration. The tonic activity of the diaphragm could be increased further by both lung inflation [2,10] and deflation [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation